Финансиските иновации како предизвик за функционирањето на финансиските институции и нивно вклопување во финансиската регулација - Гогова Самоников, Марија (Економски факултет, УКИМ, Скопје, 2013)
The financial system is an ensemble that acts in and from the surrounding which is constantly changing. Changing the surrounding of financial markets, as well as changing the market its self brings consequences that appear as an application of the new instruments and working methods. All those changes have to be registered somewhere in order for them to be managed, coordinated and controlled. Financial system control is the essence of a healthy economy. Therefore, an up-to-date and transparent regulation is a reflection of a healthy, planned ad accomplished economy. The goal of this paper is perception of the existing financial institutions and instruments and their interactive relation in the financial system and analysis of modern approaches and methods using the financial institutions and the mode of use of the instruments as a response of the existing financial structure and its surrounding; perception of the influence financial innovations have and the mode that financial institutions include innovations in their work; perception of the need for financial regulation in the overall financial system, including financial derivates – as a more specific result from the financial innovations; analysis for potential financial and economic imbalances that can be caused by not taking in consideration the implementation of the financial derivates in the financial and economic system; identification of the location of Macedonian financial structure and potential adjustments of the financial regulation towards the financial innovations.
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: financial innovations, financial instruments, financial derivates, e-finances, financial regulation